'A world of many Souths': (anti)Blackness and historical difference in conversation with Ananya Roy. Issue 6 (2nd July 2020) - Roy, Ananya; Wright, Willie J.; Al-Bulushi, Yousuf; Bledsoe, Adam
ABSTRACT: On 2–3 October 2018, an interdisciplinary group of scholars and community organizers were invited to participate in "(anti)Blackness in the American Metropolis, " 2-day workshop in Baltimore, Maryland. Each shared research on the effects of anti-Blackness policies and practices in U.S. cities and place-based organizing tactics designed to address and refute them. The event sought to merge a gap in the study of urban black communities exiting between Black Studies and Geography. The event culminated in a keynote address by Dr. Ananya Roy on the political potential of forging intellectual and communal relationships across the Global South. This interview, conducted in the aftermath of the workshop, extends Dr. Roy's address. Here, she discusses her personal and political growth, her recent intellectual interface with the Black Radical Tradition, as well as her rationale for participating in this inaugural workshop.